2023
DOI: 10.1111/jdv.19682
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival, effectiveness and safety of ixekizumab for moderate‐to‐severe psoriasis up to 5 years

L. Mastorino,
P. Dapavo,
L. Burzi
et al.

Abstract: IntroductionIxekizumab proved to be effective and safe for psoriasis treatment in several randomized clinical trials and real‐life studies. Nevertheless, long‐term real‐world experiences are still lacking, with little data up to 4 years of treatment.ObjectivesTo analyse survival, effectiveness and safety of ixekizumab in a real‐life cohort of patients affected by moderate‐to‐severe psoriasis or psoriatic arthritis up to 260 weeks (5 years).MethodsWe included all patients treated with ixekizumab from December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Also, in terms of absolute PASI, our study highlighted a higher percentage of patients who achieved a PASI of 2 or less after 5 years of treatment compared to data from clinical trials (92.41% compared with 73.6%) [ 4 ]. Our findings are very similar to those of Mastorino et al, who observed PASI 90 and PASI 100 in 81.8% and 59.1% of the 22 patients who completed 5 years of treatment [ 9 ].
Fig.
…”
Section: Discussionsupporting
confidence: 92%
“…Also, in terms of absolute PASI, our study highlighted a higher percentage of patients who achieved a PASI of 2 or less after 5 years of treatment compared to data from clinical trials (92.41% compared with 73.6%) [ 4 ]. Our findings are very similar to those of Mastorino et al, who observed PASI 90 and PASI 100 in 81.8% and 59.1% of the 22 patients who completed 5 years of treatment [ 9 ].
Fig.
…”
Section: Discussionsupporting
confidence: 92%
“…Summary drug survival curves in blue, separate studies in grey. A Secukinumab [ 24 26 , 33 , 34 , 39 41 , 44 , 46 , 48 , 50 , 51 , 53 , 62 , 64 , 68 , 70 , 72 , 74 , 80 85 ], B ixekizumab [ 23 , 32 , 33 , 39 , 40 , 42 44 , 46 , 49 , 62 , 70 , 81 , 84 , 85 ], C brodalumab [ 39 , 40 , 58 , 62 , 84 87 ], D guselkumab [ 29 , 30 , 33 , 35 , 37 , 43 , 44 , 50 , 59 , 70 , 84 , 85 , 88 , 89 ], E risankizumab [ 27 , 50 , 84 , 85 , 90 ], ...…”
Section: Resultsmentioning
confidence: 99%